Consumer Protection Against Electronic Goods Damage: A Case Study of JNE Expedition Indonesia - Nadilla Azzachrani; Fendi Setyawan; Yusuf Adiwibowo (YURIS: Journal of Court and Justice, 2026)
The rapid expansion of e-commerce in Indonesia has increased reliance on logistics service providers, yet the multi-party structure of marketplace transactions creates accountability gaps that leave consumers inadequately protected when goods are damaged in transit. This study examines three interrelated issues: the legal relationships among sellers, logistics providers, and consumers in online transactions; the normative basis for consumer protection where electronic goods are damaged during delivery; and the dispute resolution mechanisms available to affected consumers. Employing a normative juridical research design with statute and conceptual approaches, this study analyses the applicable Indonesian legal framework, including Law Number 8 of 1999 concerning Consumer Protection, the Indonesian Civil Code, Law Number 19 of 2016 concerning Electronic Information and Transactions, Law Number 7 of 2014 concerning Trade, Government Regulation Number 71 of 2019, and Ministerial Regulation Number KM 5 of 2005 concerning the Operation of Courier Services. The findings establish that the legal relationship between sellers and consumers constitutes a sale and purchase agreement, the relationship among sellers, logistics providers, and consumers constitutes a goods delivery relationship, and the relationship among the marketplace, seller, and logistics provider constitutes a tripartite cooperation arrangement. The study further finds that while the statutory framework provides a legally sufficient basis for consumer claims, structural fragmentation of responsibility across parties undermines effective redress in practice. These findings extend prior scholarship by identifying a specific accountability gap at the intersection of platform governance and logistics regulation that warrants targeted legislative reform.